The presence of Epstein-Barr virus significantly impacts the transcriptional profile in immunodeficiency-associated Burkitt lymphoma - Navari, Mohsen; Etebari, Maryam; De Falco, Giulia; Ambrosio, Maria Raffaella; Gibellini, Davide; Leoncini, Lorenzo; Piccaluga, Pier Paolo (Frontiers in Microbiology, 2015)
Burkitt lymphoma (BL) is an aggressive neoplasm derived from mature, antigen-experienced B-lymphocytes. Three clinical/epidemiological variants have been recognized, named sporadic, endemic and immunodeficiency-associated BL (ID-BL). Although they are listed within a unique entity in the current WHO Classification, recent evidence indicated genetic and transcriptional differences among the three sub-groups. Further, the presence of latently persisting Epstein-Barr virus (EBV) has been associated with specific features in endemic and sporadic cases. In this study, we explored for the first time whether EBV integration could be related with specific molecular profile in immunodeficiency-associated cases. We studied 30 BL cases, including 9 occurring in HIV-positive patients (5 EBV-positive and 4 EBV-negative) by gene and microRNA (miRNA) expression profiling. We found that ID-BL presented with different profiles based on EBV presence. Specifically, 252 genes were differentially expressed, among them being some involved in intracellular signaling and apoptosis regulation. Furthermore, 28 miRNAs including both EBV-encoded (N=18) and cellular (N=10) ones were differentially regulated. Of note, genes previously demonstrated to be targeted by such miRNA were consistently found among differentially expressed genes, indicating the relevant contribution of miRNA to the molecular profile of the examined cases. Grippingly, 17 out of the 252 differentially expressed genes turned out to be potentially targeted by both cellular and EBV-encoded miRNA, suggesting a complex interaction and not excluding a potential synergism. In conclusion, we documented transcriptional differences based on the presence of EBV in ID-BL, and suggested a complex interaction between cellular and viral molecules in the determination of the global molecular profile of the tumor.